Multi-Substrate Radiocarbon Data Constrain Detrital and Reservoir Effects in Holocene Sediments of the Great Salt Lake, Utah. Issue 4 (14th June 2019) - Bowen, Gabriel J; Nielson, Kristine E; Eglinton, Timothy I
ABSTRACT: The radiocarbon ( 14 C) content of simultaneously deposited substrates in lacustrine archives may differ due to reservoir and detrital effects, complicating the development of age models and interpretation of proxy records. Multi-substrate 14 C studies quantifying these effects remain rare, however, particularly for large, terminal lake systems, which are excellent recorders of regional hydroclimate change. We report 14 C ages of carbonates, brine shrimp cysts, algal mat biomass, total organic carbon (TOC), terrestrial macrofossils, and n -alkane biomarkers from Holocene sediments of the Great Salt Lake (GSL), Utah. 14 C ages for co-deposited aquatic organic substrates are generally consistent, with small offsets that may reflect variable terrestrial organic matter inputs to the system. Carbonates and long-chain n -alkanes derived from vascular plants, however, are ∼1000–4000 14 C years older than other substrates, reflecting deposition of pre-aged detrital materials. All lacustrine substrates are 14 C-depleted compared to terrestrial macrofossils, suggesting that the reservoir age of the GSL was > 1200 years throughout most of the Holocene, far greater than the modern reservoir age of the lake (∼300 years). These results suggest good potential for multi-substrate paleoenvironmental reconstruction from Holocene GSL sediments but point to limitations including reservoir-induced uncertainty in 14 C chronologies and attenuation and time-shifting of some proxy signals due to detrital effects.